Development and optimisation of an articulation system to improve intersection turning speed of bus rapid transit vehicle. (2015) - Cai, Yu-Meng; Jiang, You-Liang; Zhang, Shi-Jin; Chen, Shi-An
Most bus rapid transit (BRT) vehicles are often slowed down to avoid carriage-folding collisions and carriages not aligning during turning operation, which drops the capacity of intersection and even causes traffic jam. To improve the speed of the BRT vehicle running in the intersection turning route, a new type of articulation system transferring the damping torque and the stiffness torque was developed and optimised. First, the steering dynamics model of the BRT vehicle was established. Second, dynamic steering simulations of the BRT vehicle running in the intersection route with varying parameters were carried out. Lastly, the damping parameter and the stiffness parameter were optimised. The best BRT vehicle steering dynamics performance is achieved at a 12 m/s speed when the damping parameter and the stiffness parameter are set to 3060 N·s/m and 603, 490 N/m, respectively.